Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

Continuités et ruptures dans le mouvement féministe québécois francophone pour des droits sexuels et reproductifs - Jacquet, Caroline; Pagé, Geneviève; Pirotte, Magaly (Nouvelles Questions Féministes, 2017)
Cet article analyse différents moments du mouvement québécois francophone en faveur de la santé et des droits sexuels et reproductifs à travers le prisme analytique de la justice reproductive. Il s'articule autour de deux critiques développées à l'encontre du mouvement mainstream pro-choix étatsunien, soit la focalisation sur l'avortement et l'absence d'intégration d'une analyse complexe de l'imbrication des rapports de pouvoir déterminant les différentes limites auxquelles font face les femmes en matière de santé et de droits sexuels et reproductifs. À l'opposé d'un schéma historique linéaire, il brosse un portrait nuancé des outils théoriques développés dans le champ féministe et des transformations de la pratique militante que les auteures analysent à quatre moments précis : la lutte pour l'avortement libre et gratuit dans les années 1970 et 1980, la Coalition «Avortons leur congrès!» en 2005, le renouvellement en cours du cadre théorique de la Fédération du Québec pour le planning des naissances et le collectif La Riposte féministe (2016).
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; avortement; canada; droits des femmes*; histoire et politique; intersectionnalité; inégalités; justice reproductive; justice sociale; militance; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Advocating from the margins: The reproductive justice movement and the politics of oppositional consciousness - Kirwood, Zachary (Wesleyan University, 2012)
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; droits des femmes*; histoire et politique; intersectionnalité; justice reproductive; mémoires/thèses; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; états-unis; étude qualitative

Les tactiques féministes confrontées aux « tirs amis » dans le mouvement des femmes en Irlande - Taylor, Judith (Politix, 2007)
Cet article examine les modèles courants d’intelligibilité de l’interaction tactique entre les acteurs des mouvements sociaux et montre leur insuffisance pour rendre compte de l’invention tactique dont a dû faire preuve le mouvement des femmes en Irlande. Une analyse des efforts déployés par les féministes irlandaises pour l’extension du droit à l’avortement met en question l’idée que les innovations tactiques ne répondraient qu’aux contre-mouvements ou à la répression de l’État. L’expression « tir ami » fait référence au processus par lequel des groupes qui ne sont pas en opposition avec un mouvement, mais qui n’en font pas non plus partie, constituent une menace pour les finalités de ce mouvement. L’observation de la campagne féministe, de ses meetings et de l’ensemble de sa mise en scène politique donne des aperçus significatifs sur les effets des tirs amis et, spécifiquement, sur le rôle des hommes dans les mouvements de femmes.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; avortement; care; corps; cours; discipline; droits des femmes*; europe; intersectionnalité; irlande; justice reproductive; justice sociale; pol5185; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques